1990
DOI: 10.1073/pnas.87.12.4504
|View full text |Cite
|
Sign up to set email alerts
|

Proofreading in vivo: editing of homocysteine by methionyl-tRNA synthetase in Escherichia coli.

Abstract: Previous in vitro studies have established a pre-transfer proofreading mechanism for editing of homocysteine by bacterial methionyl-, isoleucyl-, and valyl-tRNA synthetases. The unusual feature of the editing is the formation of a distinct compound, homocysteine thiolactone. Now, twodimensional TLC analysis of 35S-labeled amino acids extracted from cultures of the bacterium Escherichia coli reveals that the thiolactone is also synthesized in vivo. In E. coli, the thiolactone is made from homocysteine in a reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 20 publications
(17 reference statements)
3
132
0
1
Order By: Relevance
“…This reaction is inhibited strongly in the presence of methionine, since methionine competes efficiently with Hcy for binding to the enzyme (10). To determine whether the inhibitory effects of Hcy required the formation of homocysteine thiolactone, we performed growth experiments with Hcy in the presence or absence of either 0.2 or 2 mM methionine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is inhibited strongly in the presence of methionine, since methionine competes efficiently with Hcy for binding to the enzyme (10). To determine whether the inhibitory effects of Hcy required the formation of homocysteine thiolactone, we performed growth experiments with Hcy in the presence or absence of either 0.2 or 2 mM methionine.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that Hcy may have more complex effects on cell physiology at higher concentrations. Hcy is known to compete with methionine and isoleucine for binding to their respective tRNA synthetases (10,13), and it could be that at higher Hcy concentrations this competition depletes the cell of charged tRNA species, resulting in reduced rates of protein synthesis. Under these conditions homocysteine thiolactone is likely to accumulate in the cytoplasm due to the editing function of the methionyl and isoleucyl tRNA synthetases (13).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian systems are similar to E. coli with respect to the role that methionyl-tRNA synthetase plays in methionine incorporation into proteins [167]. Studies on E. coli have demonstrated that, due to competition of homocysteine with methionine in the process that assembles amino acid chains, one molecule of homocysteine is edited to produce homocysteine thiolactone per 109 molecules of methionine incorporated into protein in vivo [168]. Thus, an excess need for protein synthesis would lead to an excess synthesis of homocysteine thiolactone.…”
Section: Heparan Sulfate Proteoglycans and Glucose Metabolismmentioning
confidence: 99%
“…It follows that, at this step alone, the synthesis of a polypeptide containing n amino acid residues consumes the equivalent of (2n) ATP. However, an incorrect amino acid and\or tRNA might also be activated or charged (Hopfield, 1974 ;Hopfield et al, 1976 ;Savageau & Freter, 1979 ;Cramer & Freist, 1987 ;Jakubowski, 1995 ;Freist, Sternbach & Cramer, 1996). The accuracy of this step of protein synthesis (amino acid selection by tRNA synthetases) is increased by, inter alia, proofreading\editing pathways whereby the misactivated aminoacyl-adenylate and\or aminoacyl-tRNA complexes are rejected by a mechanism which involves an additional ATP hydrolysis (Hopfield, 1974 ;Hopfield et al, 1976 ;Savageau & Freter, 1979 ;Mulvey & Fersht, 1977 ;Fersht, 1986 ;Jakubowski & Goldman, 1992 ;Freist et al, 1996).…”
Section: Biosynthetic Costs Of Proteinsmentioning
confidence: 99%